Use of open source projects to build an integrated smart home - Marhan, Michal (2020)
The consumer market with smart home products is expanding. To create a smart home in the past was to use expensive proprietary solutions from smart home integrators. Today, many smart home devices can be bought in ordinary stores with computer electronics. But this market is still in its infancy. There is no single unified protocol, which would be used across all those available devices. The goal defined by the author in this paper is to create a design of a smart home hub using open-source software, which can even today integrate devices across different protocols. Paper is split into theoretical and practice part. It starts with an overview of the current state of the market, then explaining the chosen methodology of system design. The analysis phase looks into details of protocols used in smart home devices, their available open-source implementations, and other software needed to make the smart home hub work. Based on the analysis the paper proceeds into the practical part when a proposal of the solution is devised, and every chosen component of the system is described. In the next phase, every step in the implementation process is documented. The final phase then tests the implementation against testing scenarios, which verifies readiness of the implementation and its ability to be moved into a production environment. The system successfully passes the test phase and is already used in one running instance. The result is a local smart home hub, which integrates devices across protocols and allows their control from one unified graphic interface.